ESL LEARNERS’ COGNITIVE AND METACOGNITIVE VOCABULARY STRATEGIES - Xodjiyeva , Ra’noxon Akmalovna; Abdugaffarova, Arofat Shamsiddinovna (Innovative Development in Educational Activities, 2023)
Vocabulary strategies are useful in learning and teaching. There are different strategies that can be used in learning and teaching lexis. However cognitive and metacognitive vocabulary learning strategies are important because they promote a deeper level of learning and understanding of the language being studied. By using self-regulated learning strategies, such as metacognitive techniques, learners can become active in the learning process, instead of passively absorbing language words and structures.